Process Identification and Operational Efficiency Improvement in a Restaurant Chain : A Case Study of Cruz Group - Gavino, Emily; Martínez, Felipe; Rathouský, Bedřich; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This bachelor’s thesis aims to explore operational inefficiencies in a growing restaurant chain, analyzing Cruz Group as a subject to improve its processes and enhance operational efficiency. The study's theoretical background focuses on restaurant operations and common problems as a start-up. It defines the use methodology frameworks DMAIC, SIPOC, Pareto, Lean, and Six Sigma. DMAIC is applied to the selected process of a restaurant with its proper definition for analysis. Data collected from real-time restaurant operations provide insights into the restaurant’s inefficiencies. Tools are used to improve workflows, optimize resource allocation, and improve customer satisfaction. Recommendations include adopting the lean tool (Mieruka) visual management to enhance critical-to-quality (CTQ) parameters. Ultimately, a control system is provided to have continuous and successful results.
Vedoucí práce: Felipe Martínez
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses